Description of the male of Cyana nigrilineata (Hampson, 1900) (Lepidoptera, Erebidae: Arctiinae), a little-known species endemic to Sumatra Island - Koshkin, Evgeny S. (Zootaxa, 2023)
First description of the hitherto unknown male of Cyana nigrilineata (Hampson, 1900) (Lepidoptera, Erebidae: Arctiinae) is presented. This species is similar to Cyana malayensis (Hampson, 1914) and C. barisana Roesler & Küppers, 1976 in external features and the structure of the male genitalia. These three species co-occur in Sumatra Island.